(untitled) (Physical Education, Health and Social Sciences, 2024)
The purpose of this cross sectional study was to assess the status of nutrition of primary school kids from the disadvantaged region of Gilgit-Baltistan, Pakistan. The study involved a sample of primary school students (N = 815). Using the anthropometry protocols by WHO (2019), two key indicators of nutrition, Height, and Weight of the primary school students were measured. Both descriptive and inferential statistical tools were used to analyse the data. To assess the existing status; Height for Age Z scores (HAZ) was calculated through WHO Anthro Plus software 2007 and Body Mass Index (BMI) percentile values were calculated. Rresults revealed that the overall prevalence of stunting among primary school students was as high as 63%, with a significant gender disparity (higher among females). Among the school going children 55.5% children were found to be underweight while only 24.7% ‘healthy’. In the ‘Severely Stunted’ group, Gilgit district had higher number of students, that is, 57% (171/413), and District Skardu had 43% (130/402). Higher rates of undernutrition observed among students enrolled in public schools than the private schools. The findings of this study underscore the urgent need for targeted interventions to improve the nutritional status of primary school students, particularly among girls and those attending public schools to reduce the malnutrition. In addition, the effectiveness of the already being-run-programs’ also need to be assessed, reassessed for their effective utilization.